2011
DOI: 10.1162/jocn.2009.21362
|View full text |Cite
|
Sign up to set email alerts
|

Cross-domain Effects of Music and Language Experience on the Representation of Pitch in the Human Auditory Brainstem

Abstract: Neural encoding of pitch in the auditory brainstem is known to be shaped by long-term experience with language or music, implying that early sensory processing is subject to experience-dependent neural plasticity. In language, pitch patterns consist of sequences of continuous, curvilinear contours; in music, pitch patterns consist of relatively discrete, stair-stepped sequences of notes. The primary aim was to determine the influence of domain-specific experience (language vs. music) on the encoding of pitch i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
307
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(327 citation statements)
references
References 49 publications
17
307
3
Order By: Relevance
“…Previous studies differed in the cut-off criterion used to define musicianship in young adults. The inclusion criteria for musicians range from 6 to 10 years of musical training (e.g., Bidelman et al, 2011;Strait et al, 2010;Wayland et al, 2010). We took the lower end and defined "musicians" as amateur instrumentalists or vocalists with at least 6 years of continuous formally instructed musical training throughout their lifetime (Wayland et al, 2010;Chan et al, 1998).…”
Section: Participantsmentioning
confidence: 99%
“…Previous studies differed in the cut-off criterion used to define musicianship in young adults. The inclusion criteria for musicians range from 6 to 10 years of musical training (e.g., Bidelman et al, 2011;Strait et al, 2010;Wayland et al, 2010). We took the lower end and defined "musicians" as amateur instrumentalists or vocalists with at least 6 years of continuous formally instructed musical training throughout their lifetime (Wayland et al, 2010;Chan et al, 1998).…”
Section: Participantsmentioning
confidence: 99%
“…The results of our study complement a growing body of research indicating that long-term experience in the discrimination and identification of pitch-evoking stimuli, obtained through the acquisition of a tone language or musical practice, modifies auditory processing at the level of the brainstem (see Tzounopoulos and Kraus 2009; Krishnan and Gandour 2009 for reviews). These studies have shown that speakers of tone languages (Krishnan et al 2005(Krishnan et al , 2010 and musicians (Wong et al 2007;Bidelman et al 2009) have enhanced subcortical phase locking to the envelope of periodic sounds in comparison to English speakers without musical experience. In speakers of a tone language, these effects are present for both speech-like and non-speech stimuli, and are greater for tonal segments with highly accelerated F0 contours (Xu et al 2006;Swaminathan et al 2008;Krishnan et al 2009b), which are characteristic of tone languages (Eady 1982).…”
Section: Subcortical Plasticity In the Auditory Systemmentioning
confidence: 99%
“…Musicians (Wong et al 2007;Bidelman et al 2009) and speakers of a tone language (Krishnan et al 2005(Krishnan et al , 2009aSwaminathan et al 2008) show more robust subcortical "phase locking" in response to pitchevoking sounds compared to English speakers without musical experience. This has been demonstrated using scalp recordings of the frequency following response (FFR), an evoked potential which reflects neural phase locking of brainstem nuclei (inferior colliculus and lateral lemniscus, Smith et al 1975;Gardi et al 1979) to the envelope of a sound.…”
Section: Introductionmentioning
confidence: 99%
“…differentiate speech sounds to a greater extent (65)(66)(67), track stimulus pitch more accurately (68,69), and are more consistent across trials (59,70). In adolescence, music training leads to faster responses to speech in noise (71), but the extent to which adolescent music training can confer other aspects of the musician signature remains unknown.…”
mentioning
confidence: 99%